2017
DOI: 10.1073/pnas.1621185114
|View full text |Cite
|
Sign up to set email alerts
|

WAVE1 in neurons expressing the D1 dopamine receptor regulates cellular and behavioral actions of cocaine

Abstract: Wiskott-Aldrich syndrome protein (WASP) family verprolin homologous protein 1 (WAVE1) regulates actin-related protein 2/3 (Arp2/3) complex-mediated actin polymerization. Our previous studies have found WAVE1 to be inhibited by Cdk5-mediated phosphorylation in brain and to play a role in the regulation of dendritic spine morphology. Here we report that mice in which WAVE1 was knocked out (KO) in neurons expressing the D1 dopamine receptor (D1-KO), but not mice where WAVE1 was knocked out in neurons expressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 74 publications
(105 reference statements)
2
17
0
Order By: Relevance
“…Our results indicate that Rac1 was mainly responsible for METH-induced spine plasticity in D1-MSNs. A recent study demonstrated that conditional knockout of WAVE1 in D1-MSNs but not D2-MSNs attenuated cocaine-induced CPP 72. Morover, another study revealed that the activation of Rap1 in D1-MSNs contributed to cocaine-induced CPP 73.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that Rac1 was mainly responsible for METH-induced spine plasticity in D1-MSNs. A recent study demonstrated that conditional knockout of WAVE1 in D1-MSNs but not D2-MSNs attenuated cocaine-induced CPP 72. Morover, another study revealed that the activation of Rap1 in D1-MSNs contributed to cocaine-induced CPP 73.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic spine density in the NAc core and shell was markedly increased by cocaine (30 mg/kg per day, i.p.) given for 5 consecutive days followed by 2 injection-free days for 4 weeks in total 41 , while a lower dosage (15 mg/kg per day for 8 consecutive days) increased spine density only in the shell 42 and in another study, cocaine (15 mg/kg per day for 14 consecutive days) induced significant increases in dendritic spine density in the NAc core but had only minimal effects in the NAc shell 43 . Based on the results of these studies, we decided to test the effects of cocaine at the dose of 30 mg/kg (or saline) daily for 14 days (see Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Although the molecular machinery that regulates actin polymerization in neurons is not fully characterized, different actin nucleators, including the Arp2/3 complex (Zuo et al, 2017) and its NPFs N-WASP (Pinyol, 2007; Ceglia et al, 2017), WAVE1 (Firat-Karalar & Welch, 2011) and WAVE 2 (Hoeng et al, 2008), as well as the tandem actin-monomer-binding nucleator Cordon-bleu (Coutts et al, 2009) were shown to positively regulate the stages of neuronal development through their role in growth cone formation and dynamics. In contrast, we found that knockout of CA (Arp2/3 binding site) on JMY gene obviously affected blastocystformation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility was that JMY acts as an upstream effector of ZGA genes such as Hsp70.1 , eIF-1A , mUerv-l and MTIA . Actin-nucleating proteins are regulated by small GTPases, protein–protein interactions, and/or posttranslational modifications, and it is likely that JMY is also regulated by similar mechanisms (Ceglia et al., 2017). Another intriguing question is why JMY combines two uniquely different cellular functions-transcriptional regulations and actin assembly in one protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation